First, find the value of f(3) and g(2). Then, substract them.
Substitute x=3 in the expression for f(x) to find the value of f(3):
![\begin{gathered} f(x)=3x-4 \\ \Rightarrow f(3)=3(3)-4 \\ =9-4 \\ =5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/godqrnvlgk2d9djej8r7dc95yhfh3nhnyu.png)
Then:
![f(3)=5](https://img.qammunity.org/2023/formulas/mathematics/college/q1kb492q72gxva6pnwifsjrksow0lfeym0.png)
Substitute x=2 in the expression for g(x) to find the value of g(2):
![\begin{gathered} g(x)=x^2 \\ \Rightarrow g(2)=2^2 \\ =4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2u7ru5zv2djyqbbgmry2t153m00pty4u8z.png)
Then:
![g(2)=4](https://img.qammunity.org/2023/formulas/mathematics/college/xupk8ngi3b7wkwycj9xj7w19tbmhcmvryy.png)
Substitute the values of f(3) and g(2) to find f(3)-g(2):
![\begin{gathered} f(3)-g(2)=5-4 \\ =1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yairk7mi9zpd7xqi5aypyxzoglsrusv9vo.png)
Therefore:
![f(3)-g(2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/at4ezsrrop5za7omnnp1u8k9x9vs226mty.png)